Derivatives of 6-(isocoumarin-3-yl)-4-methylumbelliferone - Shablykina, О.V.; Ishchenko, V.V.; Nagorna, Z.V.; Khilya, V.P. (Reports of the National Academy of Sciences of Ukraine, 2017)
The synthetic potential of 6-(isocoumarin-3-yl)-4-methylumbelliferone as a multifunctional mo lecule has been investigated. A number of new substances with fragments of deoxybenzoin-2′-carbonic acid, 3,4-dihydro isocoumarin, isoquinolone, 7-methoxycoumarin, 8-amino mety lum be lli ferone are obtained.